Ramillies : A Late Prehistoric Bison Kill and Campsite Located in Southeastern Alberta, Canada - Brumley, John H. (Book collections on Project MUSE., 1976)
Field studies made in 1972, 1973 and 1974 on a multioccupational bison kill and campsite located in the shortgrass plains of southeastern Alberta.